2017
DOI: 10.7324/rjc.2017.1041865
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera: A COST EFFECTIVE COAGULANT FOR DYE DEGRADATION

Abstract: The purpose of the work is to understand the effect of the ratio of Moringa olifera Seed powder and NaCl, current density, initial pH and agitation speed on color removal efficiency as well as COD removal from synthetic textile wastewater in the electro-coagulation technique using iron and steel electrodes. The suitable conditions for reducing color as well as COD were as follows: ratio of Moringa Olifera Seed powder and NaCl = 1: 1.5; current density = 15 mA/cm2; initial pH = 7-8; agitation speed = 400 rpm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In contrast, Ponnusami et al, 2007 5 andGong et al, 2005 17 reported maximum color removal efficiency at low pH. It is also found that color removal rate as well as COD removal rate increased by about 10% with an increase in adsorbent dosage from 3 to 8 g/dm 3 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Ponnusami et al, 2007 5 andGong et al, 2005 17 reported maximum color removal efficiency at low pH. It is also found that color removal rate as well as COD removal rate increased by about 10% with an increase in adsorbent dosage from 3 to 8 g/dm 3 .…”
Section: Resultsmentioning
confidence: 93%
“…Owing to toxic nature, chemical composition and volume discharged, the dye effluent disposed of various textile and dyeing industries can be considered as pollutants in Asian countries 2 and it must be treated by appropriate technique in order to save surroundings 3 . The effluent discharged from textile and dyeing industry contains toxic, mutagenic, carcinogenic chemical compounds which are harmful to live organisms and human being 4 .…”
Section: Introductionmentioning
confidence: 99%